Effect of thiabendazole on gains of stockers grazing 50% endophyte fungus-infected, tall fescue pastures - Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thiabendazole (TBZ®) wormer pellets were added to either a mineral or grain mix in two experiments with steers grazing 50% endophyte fungus-infected, tall fescue pastures. Research from other stations has suggested that TBZ® partially overcomes the toxicity of endophyte fungus. In our experiments, steers received .2 g of TBZ® per 100 lb body weight per day, but daily gain was not improved during the grazing period.
Keywords: Beef; Thiabendazole; Stockers; Fescue; Endophyte